Fabrication of CuO/Au Nanowires on a Copper Substrate for Ultra-Sensitive SERS Sensors - Anh, Tran Thi Ngoc; Danh, Sai Cong; Thu, Nguyen Thi; Hoang, Do Huy (VNU Journal of Science: Natural Sciences and Technology, 2024)
To optimize the surface-enhanced Raman (SERS) phenomenon on the surface of noble metals, gold nanoparticles were synthesized on the surface of nano-sized copper wires to enhance the dispersion of gold particles on the research surface. A simple experimental procedure was carried out in two stages. First, the thin copper substrate was lightly oxidized with ammonium persulfate in an alkaline environment, then incubated at 200 o C for 3 hours to form copper nanowires that exist stably on the substrate surface. Immediately afterward, highly uniform CuO/Au nanowires were formed by the chemical reduction of HAuCl 4 on the surface of the oxidized copper plate. The results show that gold nanoparticles of about 5 nm were attached to CuO nanowires with a length of up to 10 µm and a diameter between 100 and 300 nm. The X-ray energy dispersive spectrum demonstrated a uniform distribution of gold particles. The CuO/Au structure was used as a SERS substrate to detect methylene blue at a low concentration of 10 pM corresponding to 2 signals at the peaks 1395 cm −1 and 1625 cm −1 as the C-H and C-C deformation vibrations of the aromatic ring. The logarithms of the methylene blue concentrations were linearly proportional to their SERS signal intensity of methylene blue at the peak of 1625 cm -1   with a value R2 = 0.96. The signals of SERS for methylene blue at twelve different points on the material sample showed no significant differences in both intensity and shape of the spectrum, with an RSD value of 5.9%.